Anthropogenic nitrate attenuation versus nitrous oxide release from a woodchip bioreactor. (1st May 2022) - White, Shane A.; Morris, Shaun A.; Wadnerkar, Praktan D.; Woodrow, Rebecca L.; Tucker, James P.; Holloway, Ceylena J.; Conrad, Stephen R.; Sanders, Christian J.; Hessey, Samantha; Santos, Isaac R.
Abstract: Nitrogen loss via overland flow from agricultural land use is a global threat to waterways. On-farm denitrifying woodchip bioreactors can mitigate NO3 − exports by increasing denitrification capacity. However, denitrification in sub-optimal conditions releases the greenhouse gas nitrous oxide (N2 O), swapping the pollution from aquatic to atmospheric reservoirs. Here, we assess NO3 − -N removal and N2 O emissions from a new edge-of-field surface-flow bioreactor during ten rain events on intensive farming land. Nitrate removal rates (NRR) varied between 5.4 and 76.2 g NO3 − -N m −3 wetted woodchip d −1 with a mean of 30.3 ± 7.3 g NO3 − -N m −3 . The nitrate removal efficiency (NRE) was ∼73% in ideal hydrological conditions and ∼18% in non-ideal conditions. The fraction of NO3 − -N converted to N2 O ( r N2 O) in the bioreactor was ∼3.3 fold lower than the expected 0.75% IPCC emission factor. We update the global bioreactor estimated Q10 (NRR increase every 10 °C) from a recent meta-analysis with previously unavailable data to >20 °C, yielding a new global Q10 factor of 3.1. Mean N2 O CO2 -eq emissions (431.9 ± 125.4 g CO2 -eq emissions day −1 ) indicate that the bioreactor was not significantly swapping aquatic NO3 − for N2 O pollution. Our estimated NO3 − -N removal from the bioreactor (9.9 kg NO3 − -N ha −1 yr −1 ) costs US$13.14 per kg NO3 − -N removed and represents ∼30% NO3 − -N removal when incorporating all flow and overflow events. Overall, edge-of-field surface-flow bioreactors seem to be a cost-effective solution to reduce NO3 − -N runoff with minor pollution swapping to N2 O. Graphical abstract: Image 1 Highlights: A novel edge-of-field surface-flow bioreactor reduced agricultural NO3 − -N runoff by ∼18–∼73%. The bioreactor did not contribute significantly to N2 O emissions. The estimated cost of removal is ∼US$13 for each kg NO3 − -N attenuated. Surface-flow bioreactors can be effective in systems dominated by surface runoff.